Avaliação do custo-efetividade da fotobiomodulação na mucosite oral em pacientes com câncer de cabeça e pescoço - Campos, Thalita Molinos (2018)
Oral Mucositis (OM) is an alteration due to toxicity caused by cancer treatment. Low intensity laser therapy has anti-inflammatory, analgesic and tissue repair properties. The objective of this work was to perform a bibliometric analysis, systematic review and meta-analysis of the randomized clinical trials of the treatment of OM with laser in patients in treatment of cancer of the head and neck. The search terms "mucositis" AND "phototherapy", "laser therapy" AND "mucositis", "photobiomodulation" and "mucositis" were used to search the databases PubMed, Web of Science and MEDLINE. ", And" low level laser therapy "and" mucositis "in the last ten years. After the initial search we included only the randomized clinical trials and with two groups: one treated with laser and one placebo group. The studies were analyzed according to the criteria PRISMA and GRADE to evaluate the quality and degree of evidence. After the first selection, 13 studies in the bibliometric analysis and the same were included in the systematic review, after the systematic review, only 6 studies were included in the meta-analysis. Regarding scientific production, we observed the research groups that published clinical trials on the subject are predominantly from India and Brazil. The results of the systematic review and meta-analysis showed that the laser presented good results in clinical improvement and pain reduction, decreasing the chance of the patients to be 64% (RR = 0.36 [95% CI = 0.29-0.44]). patients develop OM with degrees of debilitating lesions. The cost-effectiveness analysis resulted in an incremental cost of R $ 3,687.53 for the laser group, with an incremental effectiveness of 132, 2 and the incremental cost-effectiveness ratio (ICER) was 27.89 for high OM cases avoided. It was concluded, therefore, that the photobiomodulation for OM in patients under treatment of head and neck cancer was clinically effective and cost-effective.